Avaliação da política pública de educação inclusiva em uma escola de ensino médio de Fortaleza - CE - Gomes, Deivid Pereira (2024)
The evaluation of the Public Policy for Inclusive Education, in times of affirmation of the rights of students with disabilities and neurodivergent people, is a necessity in Brazil, since inclusion must occur in everyday school life and not just raise debates that do not convert into effective actions. In this sense, this research aimed to evaluate the materialization of the Public Policy for Inclusive Education in the teaching-learning process of students with disabilities and neurodivergent people at a High School in Fortaleza-Ceará. In this way, we sought to understand and evaluate whether and how the inclusion of such students occurred, through actions and projects developed by managers and teaching staff to make the educational process viable, based on the observation of factors that facilitate access, permanence and school promotion, taking into account parameters related to teacher training, the existence of accessibility at the institution, the availability of various resources and the integration of these students into the school routine. An evaluative research was carried out, anchored in a qualitative approach, of the participant observation type, with the help of the field notebook instrument. From this, through observation of the routine of managers, teachers and students with disabilities and neurodivergent people, and also through the analysis of the content and the political-institutional context, we sought to find in the observed elements and in the spontaneous speeches of the subjects whether consciously or unconsciously, they perceived themselves to be reached and included by Public Inclusive Education Policies and whether these policies are integrated into the reality of that school. Furthermore, valuing a broader view of the research object, we also sought to observe the perception of managers and educators regarding the legislation that regulates these policies in Brazil. This was done in order to observe whether such legal provisions guided the actions of professionals, being incorporated into teaching practice and favoring teaching that values human diversity and opposes student exclusion. Thus, in view of the data found, the in-depth assessment, developed by Rodrigues (2008), was the method chosen to understand the different layers that make up the phenomenon under analysis. As the main finding of this study, it can be stated that the State does not respect legislation affirming the rights of people with disabilities and neurodivergent people, hindering their full social participation and, consequently, their inclusion in school and other social spheres.